2014
DOI: 10.1177/0003489414526689
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Acid Reflux and Eustachian Tube Dysfunction in Adults

Abstract: Objective: This study aimed to evaluate the relationship between nasopharyngeal pH and Eustachian tube dysfunction (ETD) in adults. Study Design: Unmatched case-control study. Methods: Forty-one subjects, 20 adults with a diagnosis of ETD and 21 healthy adults as controls, were enrolled from an outpatient clinic. All subjects had a Dx–pH probe placed near the torus tubarius in the posterior nasopharynx for 24 hours. The pH values were recorded every 0.5 second. Decreases in pH were considered as reflux events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…Increased prevalence of LPR was found in patients with CRS in several studies . Based on inclusion criteria, all our patients had both LPR and CRS, but only 2/3 had a positive pH‐probe measurement being comparable to other studies, suggesting that number of reflux episodes and clinical presentation is more relevant than the acidity of the reflux …”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Increased prevalence of LPR was found in patients with CRS in several studies . Based on inclusion criteria, all our patients had both LPR and CRS, but only 2/3 had a positive pH‐probe measurement being comparable to other studies, suggesting that number of reflux episodes and clinical presentation is more relevant than the acidity of the reflux …”
Section: Discussionsupporting
confidence: 73%
“…6,7 Based on inclusion criteria, all our patients had both LPR and CRS, but only 2/3 had a positive pHprobe measurement being comparable to other studies, suggesting that number of reflux episodes and clinical presentation is more relevant than the acidity of the reflux. 22,26 Controversial results regarding the usage of PPIs in LPR were published thus far, some showing significant reduction in symptoms, 14,15 while others have not found significant improvement when compared to the placebo. 8…”
Section: Comparisons With Other Studiesmentioning
confidence: 99%
“…The reflux contents can easily get into the middle ear in old age, which causes auditory tube dysfunction so that the ventilation of the middle ear is disturbed. Exposure to reflux in the long term without adequate treatment will increase the occurrence of OME [10–12].…”
Section: Study Results and Discussionmentioning
confidence: 99%
“…However, in the human host, bacteria resident within the nasopharynx experience an average temperature of 34°C, neutral pH, and mechanical and shear stresses due to air and liquid movement in addition to nutrient limitation. [43][44][45] In contrast, at the site of disease in the middle ear, the temperature is typically 37°C or greater if fever is present, and middle ear effusions from patients with chronic OM are uniformly alkaline in pH. 46,47 Marks et al observed temperature-dependent variations in transformation efficiency and biofilm dispersal by the nasopharyngeal commensal bacterium and OM pathogen, Streptococcus pneumoniae.…”
Section: Environmental Factors Influence Biofilm Formationmentioning
confidence: 99%